Current Advancements in Sactipeptide Natural Products - Chen, Yunliang; Wang, Jinxiu; Li, Guoquan; Yang, Yunpeng; Ding, Wei (Frontiers in Chemistry, 2021)
Ribosomally synthesized and post-translationally modified peptides (RiPPs) are a growing class of natural products that benefited from genome sequencing technology in the past two decades. RiPPs are widely distributed in nature and show diverse chemical structures and rich biological activities. Despite the various structural characteristic of RiPPs, they follow a common biosynthetic logic: a precursor peptide containing an N-terminal leader peptide and a C-terminal core peptide; in some cases,a follower peptide is after the core peptide. The precursor peptide undergoes a series of modification, transport, and cleavage steps to form a mature natural product with specific activities. Sactipeptides (Sulfur-to-alpha carbon thioether cross-linked peptides) belong to RiPPs that show various biological activities such as antibacterial, spermicidal and hemolytic properties. Their common hallmark is an intramolecular thioether bond that crosslinks the sulfur atom of a cysteine residue to the α-carbon of an acceptor amino acid, which is catalyzed by a rSAM enzyme. This review summarizes recent achievements concerning the discovery, distribution, structural elucidation, biosynthesis and application prospects of sactipeptides.